TOXIC EFFECT OF ORGANIC ARSENIC ON THE GROWTH OF SOYBEAN AND ECOLOGICAL RISK ASSESSMENT OF COMBINED ARSENIC CONTAMINATED FARMLANDS - T. Zhou; L. J. You; X. F. Wang; G. Rao; C. Wu; C. Guo; J. X. Chen (Journal of Animal and Plant Sciences, 2015)
The risk of arsenic (As) contamination in soybean farmlands in Jilin province was assessed and the effects of triphenylarsine(TPA) and phenylarsonic acid (PPA) on soybean germination, height of seedling, and organs such as root and hypocotyl were studied. Taking soybean as the assessed receptor, the ecological risk of the farmlands in this area was assessed. The results showed that TPA and PPA have toxic effects on soybean germination and soybean organs. There were significant logarithmic relationships between As-concentrations and germination rate, relative lengths of organs and corresponding inhibition ratio. With the increase of As-concentrations, the germination rate and the relative lengths reduced and the inhibition ratio increased. There were significant logarithmic or linear relationships between As- concentrations in organs of soybean seedling and the concentrations of TPA and PPA. Taking EC25 of germination inhibition as the assessment criterion for the farmlands in this area, only 1.8% of the area was determined as unacceptable for soybean growth. However the safety of ripe soybean crops as food still needs further assessment.
Keywords: High risk As-containing explosives; TPA; PPA; soybean; toxicity